The Progressive Supranuclear Palsy Clinical Deficits Scale. - Piot, Ines; Schweyer, Kerstin; Respondek, Gesine; Stamelou, Maria; Gasser, Thomas; Hermann, Andreas; Hoeglinger, Gunter; Hoellerhage, Matthias; Kimmich, Okka; Klockgether, Thomas; Levin, Johannes; Machetanz, Gerrit; et al. (Movement Disorders, 2020)
BACKGROUND: There is currently no undisputed, validated, clinically meaningful measure for deficits in the broad spectrum of PSP phenotypes. OBJECTIVE: To develop a scale to monitor clinical deficits in patients with PSP across its broad phenotypes. METHODS: The Progressive Supranuclear Palsy Clinical Deficits Scale was conceptualized to cover seven clinical domains (Akinesia-rigidity, Bradyphrenia, Communication, Dysphagia, Eye movements, Finger dexterity, and Gait & balance), each scored from 0 to 3 (no, mild, moderate, or severe deficits). User guidelines were developed to standardize its application. Progressive Supranuclear Palsy Clinical Deficits Scale scores were collected in patients fulfilling the MDS-PSP diagnostic criteria in two independent, multicenter, observational studies, both cross-sectionally (exploratory DescribePSP cohort; confirmatory ProPSP cohort) and longitudinally (12-months' follow-up, both cohorts). RESULTS: Cognitive pretesting demonstrated easy scale utility. In total, 164 patients were scored (70.4 ± 7.6 years; 62% males, 35% variant phenotypes). Mean Progressive Supranuclear Palsy Clinical Deficits Scale completion time was 4 minutes. The Progressive Supranuclear Palsy Clinical Deficits Scale total score correlated with existing scales (e.g., Progressive Supranuclear Palsy Rating Scale: R = 0.88; P < 0.001). Individual Progressive Supranuclear Palsy Clinical Deficits Scale items correlated well with similar constructs in existing scales. Internal consistency (Cronbach's alpha: 0.75), inter-rater reliability (0.96), and test-retest stability (0.99) were acceptable. The PSP-CDS showed significant 12-month change (baseline, 8.6 ± 3.6; follow-up: 10.8 ± 3.6; annualized difference: 3.4 ± 3.4; n = 49; P < 0.0001). Sample sizes required per arm for a two-arm, 1-year follow-up therapeutic trial to detect 50% change in Progressive Supranuclear Palsy Clinical Deficits Scale progression was estimated to be 65 (two-sided, two-sample t test). CONCLUSION: The Progressive Supranuclear Palsy Clinical Deficits Scale is a rapidly completed, clinimetrically sound scale for clinical care and research involving PSP. © 2020 International Parkinson and Movement Disorder Society.
EVALuna2:217873